A Software Process Model Handbook for Incorporating People's Capabilities - Acuna, Silvia T.; Juristo, Natalia; Moreno, Ana Maria; Mon, Alicia (Springer US : Imprint: Springer, 2005)
A Software Process Model Handbook for Incorporating People's Capabilities offers the most advanced approach to date, empirically validated at software development organizations. This handbook adds a valuable contribution to the much-needed literature on people-related aspects in software engineering. The primary focus is on the particular challenge of extending software process definitions to more explicitly address people-related considerations. The capability concept is not present nor has it been considered in most software process models. The authors have developed a capabilities-oriented software process model, which has been formalized in UML and implemented as a tool. A Software Process Model Handbook for Incorporating People's Capabilities guides readers through the incorporation of the individual's capabilities into the software process. Structured to meet the needs of research scientists and graduate-level students in computer science and engineering, A Software Process Model Handbook for Incorporating People's Capabilities is also suitable for practitioners in industry.